A view of science education in the Caribbean - Lancaster, Colin M. (Caribbean Regional Science Project, 1978)
This article describes developments in science education in the Caribbean. These include the development of primary science curricula in several countries, based on Piagetian development levels--the West Indian Science Curriculum (WISC) at the junior secondary level; the Caribbean Integrated Science Curriculum at the senior secondary level, and the introduction of a science curriculum into the seven teachers' colleges of the Eastern Caribbean. Among eight difficulties identified are: teacher resistance, the high wastage of science teachers, the high cost of science equipment, and the question of "productivity." Possible solutions to these problems have emerged. It concludes that three of the major needs arising out of the likely thrust towards the primary sector in the near future are: 1) the correlation of scientific abilities with Piagetian stages of development of children in the Caribbean, 2) the identification of scientific abilities of preschool children, and 3) the implications of such developments for teacher education
Keywords: Science education